How intrinsically motivating are swimming instructors/lessons in the Netherlands? An observational study through the lens of self-determination theory - Minkels, Carola; van der Kamp, John; Beek, Peter J. (Frontiers in Sports and Active Living, 2023)
Background: It is desirable that (more) children continue swimming after having completed their swimming lessons to preserve their swimming skills and water safety, and as part of an active, healthy lifestyle. This may be encouraged by stirring children’s intrinsic motivation for swimming during swimming lessons. However, it is currently unknown how intrinsically motivating swimming lessons are in Western countries. Purpose: This study examined to what extent swimming instructors in the Netherlands cater to the basic needs of autonomy, competence, and relatedness, which, according to Self-Determination Theory (SDT), promote intrinsic motivation. Additionally, it examined whether an SDT-based teaching program prompts instructors to better meet these needs, and to what extent the teaching program, the education and experience of the instructor, and group size predict the employment of SDT in swimming lessons. Methods: A total of 128 swimming lessons given by equally many instructors were observed in the Netherlands and rated on a modified version of the SDT teaching style scale to assess autonomy, competence, and relatedness support. The swimming lessons referred to four teaching programs, one of which was explicitly based on SDT. Results: Instructors exhibited autonomy-thwarting, weakly competence-supportive, and relatedness-supportive behaviors. The SDT-based teaching program scored higher on the provision of autonomy, competence, and relatedness in lessons. This finding was significant for autonomy. Teaching program was the only significant predictor of SDT employment by instructors. Conclusion: Further improvement is desirable in catering to the basic needs, particularly autonomy, which can be achieved by deliberately implementing the principles of SDT into teaching programs for swimming.